Chronic stress impairs the local immune response during cutaneous repair in gilthead sea bream (Sparus aurata, L.). (July 2017) - Mateus, Ana Patrícia; Anjos, Liliana; Cardoso, João R.; Power, Deborah M.
Highlights: A cutaneous stress axis exists in teleost fish skin. Stress associated transcripts are down-regulated by chronic stress in teleost fish skin. Chronic stress impairs teleost skin regeneration and the reestablishment of the physical barrier. The inflammatory response during cutaneous repair is suppressed by chronic stress. Abstract: Scale removal in fish triggers a damage-repair program to re-establish the lost epidermis and scale and an associated local immune response. In mammals, chronic stress is known to delay wound healing and to modulate the cutaneous stress axis, but this is unstudied in teleost fish the most successful extant vertebrates. The present study was designed to test the hypothesis that chronic stress impairs cutaneous repair in teleost fish as a consequence of suppression of the immune response. The hypothesis was tested by removing the scales and damaging the skin on one side of the body of fish previously exposed for 4 weeks to a chronic crowding stress and then evaluating cutaneous repair for 1 week. Scale removal caused the loss of the epidermis although at 3 days it was re-established. At this stage the basement membrane was significantly thicker (p = 0.038) and the hypodermis was significantly thinner (p = 0.016) in the regenerating skin of stressed fish relative to the control fish. At 3 days, stressed fish also had a significantly lower plasma osmolality (p = 0.015) than control fish indicative of reduced barrier function. Chronic stress caused a significant down-regulation of the glucocorticoid receptor ( gr ) in skin before damage (time 0, p = 0.005) and of star at 3 and 7 days (p < 0.05) after regeneration relative to control fish. In regenerating skin key transcripts of cutaneous repair, pcna, colivα1 and mmp9, and the inflammatory response, tgfβ1, csf-1r, mpo and crtac2, were down-regulated (p < 0.05) by chronic stress. Irrespective of chronic stress and in contrast to intact skin many hyper pigmented masses, putative melanomacrophages, infiltrated the epidermis of regenerating skin. This study reveals that chronic stress suppresses the local immune response to scale removal and impairs the expression of key transcripts of wound healing. Elements of the stress axis were identified and modulated by chronic stress during cutaneous repair in gilthead seabream skin.